Sing along and learn. The alphabet - Sheldon, Ken. (New York : Scholastic, 2010)
Presents simple songs and activities designed to teach children in preschool through second grade science concepts with sing along versions of each song.
Compact disc. and aduio files on shared drive...
"Easy learning songs and instant activities that teach Science concepts
"Grades PreK-2"--Cover.
Professional
Keywords: Alphabet -- Study and teaching; Alphabet -- Songs and music -- Texts; Children's songs; Teaching -- Aids and devices; Creative activities and seat work; Alphabet -- Study and teaching; Alphabet -- Songs; Children's songs; Teaching -- Aids and devices; Creative activities; Compact discs; Compact discs